2001
DOI: 10.1054/jhsb.2001.0571
|View full text |Cite
|
Sign up to set email alerts
|

Localized Amyloid Deposition in Trigger Finger

Abstract: Trigger finger is due to degeneration and thickening of the proximal portion (A1 pulley) of the flexor tendon sheath, which causes constriction of the flexor tendon. This study reports the presence of localized amyloid deposition in the tendon sheath of 11 of 47 cases (23%) of idiopathic primary trigger finger. Amyloid deposits were only found in patients aged over 46 years old and were present around cells and at sites of mucinous and fibrinoid degeneration which contained highly sulphated glycosaminoglycans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…Amyloid deposits have been identified in connective tissue beneath the synovial lining of the flexor tendon sheath in patients with idiopathic trigger finger. 25 In the general population, there seems to be a link between CTS and trigger finger, with concomitant occurrence in 16% to 61% of patients. 26 An association between CTS and trigger finger may be underappreciated in patients with amyloidosis.…”
Section: Clinical Presentation and Pathophysiology Of Amyloid Deposition In Musculoskeletal Connective Tissue (Fig 1)mentioning
confidence: 98%
See 1 more Smart Citation
“…Amyloid deposits have been identified in connective tissue beneath the synovial lining of the flexor tendon sheath in patients with idiopathic trigger finger. 25 In the general population, there seems to be a link between CTS and trigger finger, with concomitant occurrence in 16% to 61% of patients. 26 An association between CTS and trigger finger may be underappreciated in patients with amyloidosis.…”
Section: Clinical Presentation and Pathophysiology Of Amyloid Deposition In Musculoskeletal Connective Tissue (Fig 1)mentioning
confidence: 98%
“…There is precedent in the literature (Table 1) 2,16,17,25,[33][34][35][36][37][38][39] for identifying amyloidosis using the approach suggested in Figure 2. Earlier studies (from the 1950s through the 1980s) simply identified the presence of amyloid using Congo red staining, and later studies (beginning around the late 1980s) typed the protein source of amyloid using immunohistochemistry.…”
Section: Diagnosismentioning
confidence: 99%
“…Autonomic failure, including impotence, diarrhea, or constipation, orthostatic hypotension, bladder dysfunction and sweating abnormalities occurred in 67% of the patients. Otherwise, cardiac abnormalities occurred in 67%, dysphagia in 50%, dysphonia in 42%, and (9). However, to our knowledge, no trigger finger associated with specific transthyretin mutations has been reported.…”
Section: Discussionmentioning
confidence: 78%
“…It is particularly significant that fibrocartilage was present in the midsubstance of the CAL in 50% of the younger individuals, although there was no clear tendency for it to be a particular feature of individuals who were either younger or older than 20 years of age. Such fibrocartilage in a tendon or ligament is sometimes regarded as a sign of degeneration and is referred to as a form of “mucoid degeneration” by pathologists (Leadbetter et al, 1992; Mosier et al, 1999; Cordiner‐Lawrie et al, 2001). Although fibrocartilage can indeed be of pathological significance (e.g.…”
Section: Discussionmentioning
confidence: 99%